Frecuencia de parásitos intestinales y evaluación de métodos para su diagnóstico en una comunidad marginal de Medellín, Colombia (2013)
ABSTRACT: Intestinal parasitism is still a public health problem. It has not been thoroughly studied in Medellin, Colombia. Objective: To determine the prevalence of intestinal parasites in residents of a marginal community in Medellin and to evaluate the validity, efficiency and reliability of direct examination in its diagnosis. Methods: Cross-sectional study and evaluation of diagnostic tests. Data were collected from a primary information source. Proportions with their confidence intervals were calculated; non-parametric statistical tests and analysis of sensitivity, specificity, predictive values, negative likelihood ratio and kappa were done. Results: Prevalence of parasites, according to the results of the concentration test, was 74.4%. Evaluation was done for intestinal parasites in general and for the following categories: protozoa, helminthes, commensals and pathogens. Sensitivity war over 68%, specificity and positive predictive value were 100%, negative predictive value was over 74%, negative likelihood ratio was less than 0.32, kappa was greater than 0.77 and efficiency was over 90%. Conclusion: Prevalence of intestinal parasitism is as high as it was three decades ago; its solution needs prompt and effective intervention of health authorities. The tests available for its study, including direct examination of stools, are of high diagnostic value.